Prevalence of erectile dysfunction in a cohort of Italian hypertensive subjects. (17th February 2016) - Artom, Nathan; Pinna, Giuliano; Musso, Natale R.; Orlandini, Francesco; Malasoma, Paolo; Uccelli, Massimiliano; Artom, Alberto; Rabbia, Franco; Pascale, Claudio; Lantieri, Francesca; Pende, Aldo
Abstract: The aim of this study was to evaluate the prevalence of erectile dysfunction (ED) in a cohort of Italian hypertensive men and the association with clinical and biochemical data. The study involved 270 consecutive hypertensive subjects aged 40–70 years evaluated in Italian Hypertension Centers of six hospitals from Liguria and Piedmont. ED was assessed through the self-administered questionnaire of the International Index of Erectile Function. Clinical history with ongoing drug treatment, various clinical parameters, biochemical data and evidence about the presence of subclinical target organ damage was collected. Twenty-seven subjects refused to answer the questionnaire (10%). Among the 243 remained subjects, 123 presented ED (50.6%). ED was highly related to age, systolic blood pressure, pulse pressure, smoking status, statin therapy and kidney function. The addition of a thiazide diuretic to an inhibitor of the renin–angiotensin system significantly increased the prevalence of ED. The prevalence of ED increased in relation with the number of hypotensive drug classes taken by the patients. ED was highly prevalent in this cohort of Italian hypertensive subjects and was associated with other cardiovascular risk factors, such as age, smoking status and kidney function. The role of ED as an early marker of cardiovascular disease is discussed.